2011
DOI: 10.1103/physreve.83.026210
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamics of conjugate coupled Chua circuits: Simulations and experiments

Abstract: Dynamics of two Chua circuits, mutually coupled via conjugate variables, have been explored both numerically and experimentally. When the two autonomous systems were placed in the oscillatory regime the conjugate coupling provoked suppression of oscillations (amplitude death) in both systems. In contrast, if the two autonomous systems were placed in quiescent (fixed-point) states, then the effect of conjugate coupling was to generate oscillatory behavior (rhythmogenesis) in both systems. These phenomena of amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…In addition, this is particularly suited to experiments and both in electrochemical systems [71] as well as in electronic circuits [72], this coupling can be realized.…”
Section: Conjugate Couplingmentioning
confidence: 99%
“…In addition, this is particularly suited to experiments and both in electrochemical systems [71] as well as in electronic circuits [72], this coupling can be realized.…”
Section: Conjugate Couplingmentioning
confidence: 99%
“…Multi-path propagation with multiple delays was proposed to improve the efficiency in network-controlled systems [24]. Conjugate coupling was introduced to regulate the oscillation death phenomenon [25,26] and, it was also found that multi-channel coupling can provide a much larger domain for oscillation death than the case of single-channel coupling [27]. In spite of these investigations, a systematic study of the effect of multi-channel coupling on synchronization has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Two themes that have separately been explored in recent studies of nonlinear dynamical systems are relay coupling [1,2] (i.e., coupling two systems via a third) and coupling systems through conjugate (or dissimilar) variables [3][4][5]. A primary interest in such studies has been on synchronization [6] in its many different forms, from both theoretical and experimental points of view.…”
Section: Introductionmentioning
confidence: 99%